2022
DOI: 10.3389/fbioe.2022.814099
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Biomechanical Properties of the Paravertebral Muscle in Elderly Patients With Unilateral Chronic Low Back Pain: A Preliminary Study

Abstract: Background: Clinical incidences of chronic low back pain among the elderly are increasing. However, studies have not fully elucidated on changes in biomechanical properties of paravertebral muscles in patients with unilateral chronic low back pain. We evaluated the changes in biomechanical properties of painful and non-painful paravertebral muscles in elderly patients with unilateral chronic low back pain.Methods: Biomechanical properties of paravertebral muscles, including muscle tone and stiffness, in elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Parkhurst and Burnett (1994) found that proprioceptive asymmetries were associated with injuries in male firefighters. In older adults, asymmetrical biomechanical properties of paravertebral muscles are also linked to chronic LBP severity (Wu et al, 2022). The present study provided empirical data to illustrate bilateral asymmetry in back muscle stiffness among emergency responders.…”
Section: Left-right Symmetry In Muscle Stiffnessmentioning
confidence: 67%
“…Parkhurst and Burnett (1994) found that proprioceptive asymmetries were associated with injuries in male firefighters. In older adults, asymmetrical biomechanical properties of paravertebral muscles are also linked to chronic LBP severity (Wu et al, 2022). The present study provided empirical data to illustrate bilateral asymmetry in back muscle stiffness among emergency responders.…”
Section: Left-right Symmetry In Muscle Stiffnessmentioning
confidence: 67%
“…Pain and an inactive lifestyle may cause paraspinal muscle atrophy, which is significantly associated with pain. 33 In addition, previous studies have confirmed the increase in atrophy of the paraspinal muscles in clinical chronic low back pain patients. 34 In this study, the results demonstrated that the VAS of low back pain have a significant negative linear relationship with the paraspinal muscles in IS and DLS groups, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 78%
“…It could be inferred that the possible mechanism was that PI-LL mismatch could aggravate the degeneration of the PVM, and the latter was an important source of pain ( 8 , 28 , 29 ), disability ( 28 ), and lumbar instability ( 30 , 31 ). Wu et al reported that the VAS score and ODI were significantly positively correlated with the tone and stiffness of the PVM on the painful side ( 32 ). Protopsaltis concluded that PI-LL correlated with the ODI and Short Form-36 physical component score scoliosis research society (SRS) correlated with all ( 33 ).…”
Section: Discussionmentioning
confidence: 99%